Characteristic of Adenocarcinoma Lung Patients With Ros-1 Mutation Among North Sumatra Population - Ritonga, Adewita; Soeroso, Noni Novisari; Tarigan, Setia Putra (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Lung cancer is expected to be the most frequent cancer by 2020, accounting for over 2 million diagnoses and approximately 1.8 million deaths globally. Lung cancer, the most prevalent cancer, is identified by histopathological characteristics such as ROS-1 mutations, which impact 0.9% to 2.6% of adenocarcinomas worldwide with no data from Indonesia. The aim of this study is to examine the clinical characteristics of patients with ROS-1-mutant adenocarcinomas. A study with a cross-sectional design. Clinical characteristics of patients include their gender, history of smoking, family history of cancer, clinical stage, and the histological grading of their adenocarcinoma in hospitals. ROS-1 using RT-PCR in conjunction with paraffin blocks. A total of 90 adenocarcinoma patients were included in the study. The majority of patients were male (66.7%), aged 41–60 years (55.6%), former smokers (67.8%), and had no family history of cancer (97.8%). The highest malignancy level was at stage IVA (82.2%), with poorly differentiated histopathological grading being the most common (53.3%). The detection of ROS-1 fusion in 2% of patients emphasizes the need for molecular analysis in assessing individual genetic risk. ROS-1 fusion detection was obtained in 2% of female patients who were younger (average age 50 years) and never smoked. Only 2% of patients in the North Sumatra region met the criteria for ROS-1 fusion, including being female, being younger than the average patient age of 50, and not smoking.